Bipolar Switching Properties of the Transparent Indium Tin Oxide Thin Film Resistance Random Access Memories - Kai-Huang Chen; Chien-Min Cheng; Mei-Li Chen; Yi-Yun Pan (Nanomaterials, 2023)
In this study, the bipolar switching properties and electrical conduction behaviors of the ITO thin films RRAM devices were investigated. For the transparent RRAM devices structure, indium tin oxide thin films were deposited by using the RF magnetron sputtering method on the ITO/glass substrate. For the ITO/ITOX/ITO/glass (MIM) structure, an indium tin oxide thin film top electrode was prepared to form the transparent RRAM devices. From the experimental results, the 102 On/Off memory ratio and bipolar switching cycling properties for set/reset stable states were found and discussed. All transparent RRAM devices exhibited the obvious memory window and low set voltage for the switching times of 120 cycles. The electrical transport mechanisms were dominated by the ohmic contact and space charge limit conduction (SCLC) models for set and reset states. Finally, the transmittances properties of the transparent ITO/ITOX/ITO RRAM devices for the different oxygen growth procedures were about 90% according to the UV–Vis spectrophotometer for the visible wavelength range.